The Kansas Nurse Leader Residency Program: Building Nurses' Capacity to Lead Change. Issue 5 (September 2018) - Peltzer, Jill N.; Shen, Qiuhua; Pierce, Janet; Selig, Brian; Hober, Christine; Carlton, Elizabeth; Teel, Cynthia
Abstract : As nurses engage as partners in addressing complex healthcare issues, it is increasingly important to develop nurse leaders. Many nurses need expanded knowledge and training to lead change. The purpose of this article is to describe an innovative statewide nurse leadership residency program to prepare new nurse leaders in four specialty areas. Suggestions are offered for continued advancement of leadership training for RNs across specialty roles and settings.